Identification of Understanding Student in Solving Integral Calculus Based on Mathematical Ability - Siti Napfiah (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2021)
The purpose of this study was to identify students' lack of understanding in completing integral calculus based on students' mathematical abilities. Integral calculus material here focuses on the material integration techniques. This material is important to identify the lack of understanding experienced by prospective mathematics teacher students because they muhs be able to mahser this material because this material is found at the secondary school level where they will teach. The research method used is descriptive qualitative method. The results of the study are described in a narrative manner based on the data obtained. The subjects in this study were two people with high abilities, two people with moderate abilities, and two people with low abilities. Each ability identified their lack of understanding of integral calculus, especially material on integration techniques. Based on the research that has been done, it is concluded that the identification of students' misunderstandings in solving integral calculus problems, especially the material for integration techniques. High ability students can understand the concept of integration techniques. students with moderate abilities can claMSify integration techniques but do not understand the rational function integral techniques. Low-ability students can only understand the basic concepts of integrals but cannot understand the concepts of integration techniques.